Persepsi Siswa Terhadap Pelayanan Pegawai Perpustakaan di SMK Negeri 2 Payakumbuh - Faizul Hamdani; Syahril (Journal of Practice Learning and Educational Development, 2024)
This study was motivated by the library staff services that have not been optimal as expected at SMK Negeri 2 Payakumbuh. The purpose of this study was to obtain information about students’ perceptions of library staff services at SMK Negeri 2 Payakumbuh, as seen from circulation, reference, preservation and conservation services, and reading rooms. The type of research used is descriptive quantitative with the research population is all class XI students, at SMK Negeri 2 Payakumbuh, totaling 666 people and a sample of 87 people, the sample was drawn using the slovin formula and taken using the proportional random sampling technique. The instrument used is a Likert Scale model questionnaire which has been tested to determine its validity and reliability. The result is 37 valid questionnaire items and 3 invalid items and the research instrument is declared reliable. The data is processed using the mean formula (average). From the results of data processing, the average score of student perceptions of circulation services is 3.81, the average score of student perceptions of reference services is 3.74, the average score of student perceptions of preservation and conservation services is 3.82, and the average score of student perceptions of reading room services is 3.90. From these results it can be concluded that according to students’ perceptions of library staff services at SMK Negeri 2 Payakumbuh.